Land information systems : an overview and outline of software requirements - Price, V J S (School of Architecture, Planning and Geomatics, 2017)
This thesis looks at some aspects of land information systems. The introduction gives the rationale for this study, and the second chapter outlines the development of land information systems with particular reference to the cadastre. In the third chapter the software requirements for the development of land information systems are considered. Programming language and databases are discussed. The fouth chapter deals with the organisation and hardware needed for a land information system. Finally, in the fifth chapter some of the algorithms used in land information systems are presented. Four appendices cover the programmes which were developed in the course of this study, the software specification for an operational system, an example of LIS-related data in a large organisation, and the syntax of Modula-2, the programming language used for the examples.